THE INVOLVEMENT OF EDUCATIONAL ACTORS IN THE THREE WAY TRAFFIC COMMUNICATION SYSTEM TO IMPROVE THE QUALITY OF ELEMENTARY SCHOOL STUDENTS IN JOMBANG - Ospa Pea Yuanita Meishanti; Mar’atul Fahimah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Fast and sophisticated time-guidance impacts many fields, especially education as the initial foundation of an educational ecosystem. It can be prevented through family, school, environmental education. One effort involving teacher education actors, parents, students in System Three Way Traffic Communication to improve learning outcomes especially elementary school students. The purpose of this research is to know the effect of Three Way Traffic Communication System to the students process skill. Quantitative Method One Group Pratest- Postest Design uses 10 schools, research results: average pretest learning outcomes of some schools below 70, overall average postest satisfying average above 75, effectiveness of sensitivity index treatment 8 medium sensitivity index question, 2 about high sensitivity index, teacher’s response questionnaires, parents and learners with excellent results. From the research shows the existence of the involvement of educational actors in improving learning outcomes, the compilation of textbooks, can be used as further research forms of continuous development